2013
DOI: 10.1039/c3py00772c
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature rapid SARA ATRP of acrylates and methacrylates in alcohol–water solutions mediated by a mixed sulfite/Cu(ii)Br2 catalytic system

Abstract: The new generation of catalytic systems for Controlled/"Living" Radical Polymerization (CLRP) of vinyl monomers should be non-toxic, inexpensive and provide fast polymerizations in environmentally friendly media. Herein, we report the successful ambient temperature ATRP of several vinyl monomers (MA, n-BA, MMA and DMAEMA) catalyzed by inorganic sulfites (Na S O and Na S O) and small amounts of a Cu(II)Br /Me TREN system in alcohol-water mixtures. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 53 publications
5
93
0
Order By: Relevance
“…45 Due to its poor solubility in organic solvents, 61 the concentrations of S 2 O 4 2- anion and consequently the concentrations SO 2 •- resulting from dithionite anion dissociation are very small. In these solvents, an excess of Na 2 S 2 O 4 , was employed, 45,46 and the concentration of SO 2 •- species was maintained low and constant during the course of the polymerization. In aqueous media (more than 75% of water content) the Na 2 S 2 O 4 can be fully soluble, and consequently can generate a very high concentration of SO 2 •- species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…45 Due to its poor solubility in organic solvents, 61 the concentrations of S 2 O 4 2- anion and consequently the concentrations SO 2 •- resulting from dithionite anion dissociation are very small. In these solvents, an excess of Na 2 S 2 O 4 , was employed, 45,46 and the concentration of SO 2 •- species was maintained low and constant during the course of the polymerization. In aqueous media (more than 75% of water content) the Na 2 S 2 O 4 can be fully soluble, and consequently can generate a very high concentration of SO 2 •- species.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been obtained when sulfites were used to polymerize (meth)acrylates in organic solvents. 45,46 In the absence of the ATRP initiator (Table 2, entry 4), the polymerization was much slower (~ 230 times), which indicated that the only a very few polymer chains were initiated directly from the SO 2 •- radical anions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the Matyjaszewski's researches [17,23,24] it can be stated that the SARA ATRP mechanism is correct. SARA ATRP/SET-LRP was successfully applied to relatively nonpolar monomers (e.g., styrene [25], butyl acrylate [26], methyl acrylate [14,24,26,27], 2-(diisopropylamino) ethyl methacrylate [26,28], methyl methacrylate [19,26,29]), as well as polar monomers (e.g., oligo(ethylene oxide) monomethyl ether acrylate [13], N-isopropylacrylamide [30]) for the preparation of a variety of polymeric materials with different structures and architectures, including homopolymers, and well-defined block copolymers. However, tri-block copolymers have sparked much interest and their potential has been realized in many areas.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of Controlled/"Living" Radical Polymerization (CLRP) brought unprecedented tools to synthesize polymers with controlled structures, chain-end functionalities, architecture and narrow molecular weight distribution [16][17][18][19]. Among the CLRP methods, Atom Transfer Radical Polymerization [20] is the most used method due to several intrinsic advantages, such as: easy procedures, commercial availability of the compounds, mild reaction conditions and, more recently, residual amounts of metal complexes [21][22][23][24][25][26][27]. In this paper, we report the use of an amphiphilic copolymer based on poly(ethylene glycol) and poly(4-vinyl pyridine) blocks (mPEG-b-P4VP) [28] for dispersing photocatalytic TiO2 nanoparticles in water, followed by its ∼ ∼ incorporation in an acrylic varnish formulation.…”
Section: Introductionmentioning
confidence: 99%